Heroin addiction and skin lesions: a case report - Ünver, Hatice; Tural, Ümit (Journal of Dependence, 2015)
Heroin addiction has many negative effects in terms of society and individuals. Heroin can be used in many ways as inhalation, smoking and injection and long-term addicts can use many different injection sites for heroin. When they have difficulty of intravenous injection sites, they tend to use subcutaneous tissues and muscles for injection. Such injections can cause numerous medical problems. In this case report, we aim to discuss the follow-up process in the psychiatric inpatient services with treatment and management plan of a 10 years addicted patient who injected heroin to the subcutaneous tissues and muscles in his legs and had lesions due to injections.